2016
DOI: 10.3892/mmr.2016.5084
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant activity of the traditional herbal formula Gwakhyangjeonggi-san via enhancement of heme oxygenase-1 expression in RAW264.7 macrophages

Abstract: Gwakhyangjeonggi‑san (GHJGS) is a mixture of herbal plants, including Agastache rugosa, Perilla frutescens, Angelica dahurica, Areca catechu, Poria cocos, Magnolia officinalis, Atractylodes macrocephala, Citrus reticulata, Pinellia ternata, Platycodon grandiflorum, Glycyrrhiza uralensis, Ziziphus jujuba and Zingiber officinale. GHJGS has been used for treating diarrhea‑predominant irritable bowel syndrome in traditional Korean medicine. In the present study, the anti‑inflammatory and antioxidant effects of GHJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Investigations by Zhou et al have shown that vitamins C and E can alleviate hepatoxic effects of arecanut in mice [ 82 ]. These findings support the use of arecanut in combination with other antioxidant rich herbal ingredients in traditional medicine systems, thus alleviating any possible detrimental effects [ 74 ]. In the present study, the content of arecanut accounts only for 1/8th of the TBQ mixture, while the remaining 7/8th portion is shared by seven herbal ingredients which are rich sources of natural antioxidants [ 24 , 26 – 30 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Investigations by Zhou et al have shown that vitamins C and E can alleviate hepatoxic effects of arecanut in mice [ 82 ]. These findings support the use of arecanut in combination with other antioxidant rich herbal ingredients in traditional medicine systems, thus alleviating any possible detrimental effects [ 74 ]. In the present study, the content of arecanut accounts only for 1/8th of the TBQ mixture, while the remaining 7/8th portion is shared by seven herbal ingredients which are rich sources of natural antioxidants [ 24 , 26 – 30 ].…”
Section: Discussionsupporting
confidence: 67%
“…However, it has been demonstrated that such association depends on the frequency and the dose of arecanut consumption [ 71 , 73 ]. Despite this claimed potential carcinogenic effect, small doses of arecanut have been used alone or in combination with other medicinal herbs in treating diverse disease conditions in Asian traditional medicine systems [ 74 76 ]. A number of recent laboratory and clinical studies have also provided strong evidence for the therapeutic effect of low concentrations of arecoline, which is known to be the carcinogenic alkaloid in arecanut.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jeong et al . 40 demonstrated that AM significantly reduced production of the proinflammatory cytokines, TNF-α, IL-6 and prostaglandin E2 in LPS-stimulated RAW 264.7 murine macrophage cells and enhanced expression of HO-1 and prevented the generation of reactive oxygen species in RAW 264.7 murine macrophage cells. Zhang et al .…”
Section: Discussionmentioning
confidence: 93%
“…Several researchers have attempted to inhibit activated macrophages as a potential therapy for inflammatory disease [ 1 , 26 ]. Many studies have shown that activating macrophages with bacterial endotoxins, such as LPS, primarily triggers the production of inflammatory mediators, including NO and PGE 2 , as well as the inducible enzymes iNOS and COX-2 [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%